CREATING A DIGITAL CULTURE IN THE ORGANIZATION - Nugroho, Sukmo Hadi; Bandono, Adi; Suharyo, Okol Sri (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2023)
Digital culture allows members and the organizations that support them to grow, develop, and innovate quickly, as well as adapt to meet the needs of their customers. This research aims to develop appropriate and systematic procedural steps for creating a digital culture in an organization. The method used is the Descriptive Qualitative Analysis Method approach. The results of this research show that there are several reasons why digital culture is very important which can be described as follows: reducing barriers in communication and increasing transparency, increasing agility and greater adaptability, increasing collaboration and innovation, and increasing capabilities in terms of data collection. The results of the next research are that several best ways can be taken to realize and create a digital culture, which can be identified as follows: (1) prioritizing transparency, (2) encouraging collaboration, (3) offering digital training, (4) being comfortable with risk, and (4) aspires to inspire. Keywords: Digital Culture, Organization.